Surgical Treatment of Peri-Implantitis: A 17-Year Follow-Up Clinical Case Report - Fabrizio Bassi; Pier Paolo Poli; Davide Rancitelli; Fabrizio Signorino; Carlo Maiorana (Hindawi Limited, 2015)
The purpose of the present case report was to describe the surgical treatment of a peri-implantitis lesion associated with a regenerative approach. A 48-year-old patient came to authors' attention 36 months after the placement of a dental implant (ITI-Bonefit Straumann, Waldenburg, Switzerland) in position 46. A swelling of the peri-implant soft tissues was observed, associated with bleeding on probing and probing depth > 10 mm. A significant peri-implant bone loss was clearly visible on the periapical radiograph. A nonsurgical periodontal supportive therapy was firstly conducted to reduce the inflammation, followed by the surgical treatment of the defect. After mechanical and chemical decontamination with tetracycline solution, a regenerative approach consisting in the application of deproteinized bovine bone mineral (Bio-Oss, Geistlich Pharma AG, Wolhusen, Switzerland) and a collagen membrane (Bio-Gide, Geistlich Pharma AG, Wolhusen, Switzerland) was performed. An antibiotic therapy was associated with the treatment. The 17-year follow-up showed a physiological probing depth with no clinical signs of peri-implant inflammation and bleeding on probing. No further radiographic bone loss was observed. The treatment described in the present case report seemed to show improved clinical results up to a relevant follow-up period.